2013
DOI: 10.5326/jaaha-ms-5738
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications Following TECA-LBO in the Dog and Cat

Abstract: The medical records for 133 total ear canal ablations combined with lateral bulla osteotomies (TECA-LBOs) performed on 82 dogs (121 ears) and 11 cats (12 ears) between 2004 and 2010 were reviewed to determine if the duration of preoperative clinical signs was associated with the incidence of postoperative facial nerve injury and Horner's syndrome. Other perioperative complications, such as a head tilt, nystagmus, incisional drainage, draining tracts, hearing loss, as well as bacterial culture results, were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…In the veterinary literature, facial nerve palsy and dryness of the nostrils was reported postoperatively in two (18.2%) of 11 dogs that underwent surgery for cholesteatoma. 2 In previous retrospective studies of canine TECA and LBO, 13-46% had facial nerve paresis, [30][31][32] and 4-23% had residual deficits in facial nerve function after TECA-LBO. 30,32,33 It has been reported that surgical treatment is curative in only 50% of cases of canine cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the veterinary literature, facial nerve palsy and dryness of the nostrils was reported postoperatively in two (18.2%) of 11 dogs that underwent surgery for cholesteatoma. 2 In previous retrospective studies of canine TECA and LBO, 13-46% had facial nerve paresis, [30][31][32] and 4-23% had residual deficits in facial nerve function after TECA-LBO. 30,32,33 It has been reported that surgical treatment is curative in only 50% of cases of canine cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…Primary causes of CUD in dogs include spontaneous chronic corneal ulceration (SCCED) [5, 10, 16] and canine herpes virus-1 [17]. Multiple secondary causes are reported, including entropion [18, 19], ectopic cilia [8, 20], primary and secondary forms of keratoconjunctivitis sicca (KCS) [7, 21], corneal degeneration [22], traumatic events [23–25], corneal overexposure related to general anesthesia [26], facial nerve paralysis [27] and orbital diseases [28, 29]. Many of these factors have also been associated with certain breed phenotypes [30] and some smaller studies based on referral populations of less than 250 cases have reported increased CUD prevalence in breed-types such as brachycephalic [7, 31, 32] or spaniel types [7, 33].…”
Section: Introductionmentioning
confidence: 99%
“…The development of an infected fluid-filled pocket at the surgical site of dog 1 and ongoing serous discharge in dog 3 suggests that either the substantial dead space created by surgical excision of the ear canal was not well controlled by passive drainage and sutures, or that the wounds were particularly effusive as a result of a high bacterial burden or ultrasonic curette use. The use of passive drains has been reported extensively following TECA surgery without complication (White & Pomeroy 1990, Spivack et al 2013, although the intraoperative placement of drains in routine TECA-LBO has not produced superior results to primary closure of the soft tissues (Devitt et al 1997). Given the complications in our cases the use of an active suction drain may have been beneficial in these dogs and should be considered in future patients.…”
Section: Discussionmentioning
confidence: 78%
“…The use of passive drains has been reported extensively following TECA surgery without complication (White & Pomeroy , Spivack et al . ), although the intraoperative placement of drains in routine TECA‐LBO has not produced superior results to primary closure of the soft tissues (Devitt et al . ).…”
Section: Discussionmentioning
confidence: 99%